2017
DOI: 10.1016/j.ultsonch.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted selective catalytic transfer hydrogenation of soybean oil using 5% Pd/C as catalyst under ambient conditions in water

Abstract: Catalytic transfer hydrogenation (CTH) is an alternative approach that does not require the use of potentially dangerous hydrogen gas. Pd/C is the most favoured catalyst for the selective hydrogenation of soybean oil yielding lower extent of formation of stearic acid and trans-isomer, which have adverse health effects. The present work deals with intensification of catalytic transfer hydrogenation of soybean oil in the presence of 5wt.% Pd/C using ultrasound under ambient reaction conditions. The effect of imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…When the formate ion concentration is increased to 0.40 mol/50 mL, the final iodine value obtained at the end of the reaction is only marginally different from the formate ion concentration of 0.32 mol/50 mL 26 .…”
Section: Process Parameters 311 Effects Of Formate Ion Concentrationmentioning
confidence: 80%
“…When the formate ion concentration is increased to 0.40 mol/50 mL, the final iodine value obtained at the end of the reaction is only marginally different from the formate ion concentration of 0.32 mol/50 mL 26 .…”
Section: Process Parameters 311 Effects Of Formate Ion Concentrationmentioning
confidence: 80%
“…Use of 0.16 mol/50 mL H 2 O and 0.24 mol/50 mL H 2 O of ammonium formate resulted in a much slower reaction rate. An increase in the donor quantity to 0.32 mol/50 mL water resulted in the best results , but a further increase to 0.40 mol/50 mL water showed only a marginal difference in the final iodine values that were obtained at the end of the reaction 27 . When the concentration of ammonium formate is 0.40 mol/50 mL H 2 O, the final iodine value is 101 g I 2 /100g.…”
Section: 1 Effects Of Formate Ion Concentrationmentioning
confidence: 91%
“…These results could be attributed to that water offered a medium in the reaction to form the aqueous solution film of isopropyl alcohol on the surface of Ni-Cr-B-CTAB catalyst. 9 Thus, the hydrogen donor of isopropyl alcohol could have good contact with the catalyst and the reactant of FAMEs. However, the large dosage of water used in the CTH could lead to the increase of the thickness of the aqueous solution film, inhibiting the approach of FAME with the catalyst surface and affecting the hydrogenation of FAME.…”
Section: Effect Of Water Amount On Cth Of Famesmentioning
confidence: 99%
“…Therefore, CTH can be implemented at mild reaction conditions with simple facilities and has great potential in the production of value-added hydrogenated products in recent years. 9 Mei et al 10 found that the oxidation stability and cetane number of the soybean methyl ester were improved significantly via CTH reaction using isopropanol as the hydrogen donor and Raney-Ni as the catalyst. Amin et al 11 reported the CTH of castor oil with glycerol and limonene as hydrogen donors in the presence of Pd/C catalyst at the reaction temperature of 178 C, and the results suggested that the melting point of hydrogenated castor oil increased.…”
Section: Introductionmentioning
confidence: 99%